Prosthodontic management of a patient with Gardner's syndrome: A clinical case report - Kunwarjeet Singh; Abhishek Singh; Prince Kumar; Nidhi Gupta (Wolters Kluwer Medknow Publications, 2014)
Gardner's syndrome is a genetic condition demonstrating an autosomal dominant trait and characterized by the multiple colonic polyps (familial adenomatous polyposis coli) with sebaceous cysts and jaw osteomas. Various dental abnormalities present in patient's suffering with this syndrome includes multiple impacted or unerupted teeth, supernumerary teeth, hypodontia, compound odontomes and dentigerous cyst. In this case report, a patient with Gardner's syndrome who suffered from functional and psychological problems owing to multiple impacted, unerupted teeth and hypodontia was presented. Patient was treated with a maxillary conventional overdenture opposing mandibular custom bar supported overdentures.